To the Study of the Genus Calyptronema Marion, 1870 (Nematoda, Enoplida]) (K Izucheniiu Roda Calyptronema Marion, 1870 (Nematoda, Enoplida)) - Belogurov, O. I. (Biologicheskie Nauki, 1979)
Locality: NA; Cabinet:n969
NeMys doc_id: 6091